Sex- and Region-Specific Differences in the Transcriptomes of Rat Microglia from the Brainstem and Cervical Spinal Cord - Ewald, Andrea C. (J Pharmacol Exp Ther, 2020)
The neural control system underlying breathing is sexually dimorphic with males being more vulnerable to dysfunction. Microglia also display sex differences, and their role in the architecture of brainstem respiratory rhythm circuitry and modulation of cervical spinal cord respiratory plasticity is becoming better appreciated. To further understand the molecular underpinnings of these sex differences, we performed RNA sequencing of immunomagnetically isolated microglia from brainstem and cervical spinal cord of adult male and female rats. We used various bioinformatics tools (Gene Ontology, Kyoto Encyclopedia of Genes and Genomes, Reactome, STRING, MAGICTRICKS) to functionally categorize identified gene sets, as well as to pinpoint common transcriptional gene drivers that may be responsible for the observed transcriptomic differences. We found few sex differences in the microglial transcriptomes derived from the brainstem, but several hundred genes were differentially expressed by sex in cervical spinal microglia. Comparing brainstem and spinal microglia within and between sexes, we found that the major factor guiding transcriptomic differences was central nervous system (CNS) location rather than sex. We further identified key transcriptional drivers that may be responsible for the transcriptomic differences observed between sexes and CNS regions; enhancer of zeste homolog 2 emerged as the predominant driver of the differentially downregulated genes. We suggest that functional gene alterations identified in metabolism, transcription, and intercellular communication underlie critical microglial heterogeneity and sex differences in CNS regions that contribute to respiratory disorders categorized by dysfunction in neural control. These data will also serve as an important resource data base to advance our understanding of innate immune cell contributions to sex differences and the field of respiratory neural control. SIGNIFICANCE STATEMENT: The contributions of central nervous system (CNS) innate immune cells to sexually dimorphic differences in the neural circuitry controlling breathing are poorly understood. We identify key transcriptomic differences, and their transcriptional drivers, in microglia derived from the brainstem and the C3–C6 cervical spinal cord of healthy adult male and female rats. Gene alterations identified in metabolism, gene transcription, and intercellular communication likely underlie critical microglial heterogeneity and sex differences in these key CNS regions that contribute to the neural control of breathing.